Applying Diffusion of Innovation in Online Purchase Intention through Social Network: A Focus Group Study of Facebook in Thailand - Leerapong, Atchara (Information Management and Business Review, 2013)
Although there are several studies on factors affecting online purchase intention in social media website using the Technology Acceptance Model (TAM), little research exists with respect to the study using different theories. This research is one of the studies that using an alternative theory, Diffusion of Innovation Model. This paper reports the findings of recent focus group research among working adult (ages 25 to 34), which examined the factors that influence their online purchase decision through online social network, particularly Facebook. The findings are presented and discussed in order to refine the preliminary research model that was developed from an extensive review of literature. Methods: Two focus groups involving 15 participants were recruited in Trang, Thailand. Researchers analyzed and coded the data according to research model and hypotheses. Results: Focus group respondents ranked in order of importance relative advantage, trust, perceived risk, compatibility as the factors that encouraged or discouraged them from purchasing product through Facebook. The findings of factors and their attributes from this study are in line with the findings in the literature with slight variation. Conclusions: This research makes a contribution to the development of a theoretical understanding of online purchase intention through social network.